The Role of the Top Management Team in the Choice of Entry Modes – Theoretical Perspective - Sara Jiménez Burillo; Juan J. Jiménez Moreno (Entrepreneurial Business and Economics Review)
Launching the process of internationalization is a critical decision, so using combinations of entry modes can be beneficial to sketch an easy and feasible international process. Members of TMT might have some special characteristics to achieve planned objectives and strategies and take appropriate decisions, especially combinations. The objective of the article is to present the main themes of the literature discourse on the role of entry modes and their combinations.